Stroke in Bangladesh: A Narrative Review of Epidemiology, Risk Factors and Acute Stroke Services - Mudasar Aziz; Naznin Bipasha; Udit Gupta; Isabela V. P. Ramnarine; Jessica Redgrave; Ali N. Ali; Arshad Majid; Simon M. Bell (Journal of Cardiovascular Development and Disease)
Introduction: Stroke is a major cause of mortality and disability worldwide. It is one of the foremost non-communicable diseases and the third leading cause of death in Bangladesh. Bangladesh is a developing country and as such, the prevalence, risk factors and management of the condition has some differences with more Westernised populations. In this review, we look at the epidemiology of stroke in Bangladesh and what barriers exist to improving stroke care in this country. Methods: A systematic search of the PubMed database, Mymensingh Medical Journal, Bangladesh Journal of Neuroscience and Google Scholar was conducted for articles relating to stroke in Bangladesh. Results: The incidence of stroke in Bangladesh is 3 strokes per 1000 people. The prevalence of haemorrhagic stroke is higher than in Western populations, and novel risk factors such as sitting in a squatting position and betel nut chewing increase a Bangladeshi’s stroke risk. A lack of education on stroke symptoms and a poor internal infrastructure are the main barriers to improving stroke care in this country. Conclusions: Stroke in Bangladesh is associated with traditional risk factors and non-traditional risk factors that are behaviourally ingrained into the local culture. Improved outcomes for these patients will rely on education programmes for the population, a regard for these risk factors and improving the availability of evidence-based treatments. Innovative approaches from policy decision makers to enhance equitable access to stroke services may help in providing stroke care in Bangladesh.